Regards actuels sur la muséographie d’entre-deux-guerres - François Poncelet (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
During the interwar period a remarkable evolution has been in museography of art galleries. New practices are elaborated, developed and continued for a long time – actually up to now for some. The debates in which they originated sometimes strangely resemble the discussions that animate the museums today. A look to back is necessary…